Dreamweaver. level 1 - Concepcion, Rafael; Safari eBooks ([Berkeley, Calif.?] : Peachpit Press, 2008)
"Getting started in Dreamweaver, this course covers all the basics of website design with Dreamweaver."--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed March 9, 2009).
Electronic reproduction.
Keywords: Dreamweaver (Computer file); Web sites -- Design; Electronic books